Monitoring and Analysis of Geotemperature during the Tunnel Construction - Tao Wen; Zheng Hu; Yankun Wang; Zihan Zhang; Jinshan Sun (Energies, 2022)
High geotemperatures are encountered during tunnel construction in areas with complex geological structures, which can seriously affect personnel and equipment in the process of tunnel construction and operation. The Nige tunnel, a deep-buried extra-long tunnel, was selected to monitor the geotemperature during construction. The air, rock, and water temperatures during the tunnel construction were measured at the tunnel face, and the actual temperatures of the rock or water body at the tunnel face were measured by advanced drilling. The variation trends of the water temperature, air temperature, and flow of water with the tunnel mileage were analyzed. The differences in three measured rock temperatures in three advanced drillings were revealed. The results showed that the Nige tunnel had a maximum water temperature of 63.4 °C, maximum rock temperature (Rock T) of 88.8 °C, and maximum air temperature (Air T) of 56.4 °C. Increasing trends of the air, rock, and water temperatures with the tunnel’s horizontal distance and the buried depth (vertical depth) were obvious, and the geotemperature gradient was approximately 7.6 °C per 100 m. Additionally, the variation laws of the construction ambient temperature with time in a complete construction cycle showed four stage characteristics, and each stage presented different mathematical relationships. These findings will provide guidance for the construction of high geotemperature tunnels in future.